Isolation of fungi producing Cellulases from Cocoa Pod (Theobroma Cacao L.) - Jimat, Dzun Noraini; Che Husin, Nur Fatin Diana; Azmi, Azlin Suhaida; Ahmad Raus, Raha (2013)
Cellulases are a complex inducible enzyme that able to degrade cellulose. This study investigates the isolation of fungi producing cellulase from mouldy cocoa pod (Theobroma cacao L.). Screening of cellulolytic isolates by using a congo red test were carried out on carboxymethyl cellulose (CMC) agar plates. The production of cellulases by isolated-cocoa pod fungi in fermentation using cocoa pod husks as substrate was performed. Fungal-cellulases activity of filter paper activity (FPase), carboxylmethyl cellulase (CMCase) and reducing sugar concentration were determined.